Haplotypes in the coding region of myostatin gene in broiler chicken - BHATTACHARYA, T K; CHATTERJEE, R N; KUMAR, U RAJ; SINGH, D; NIRANJAN, M; REDDY, B L N (The Indian Journal of Animal Sciences, 2012)
A study was designed to explore haplotypes of myostatin gene in control broiler chicken. The single stranded- conformation polymorphism technique was used to find out variants of exon 1, 2 and 3 of myostatin gene and all the variants were sequenced. Total 7 haplotypes were observed in the population where h1 haplotype was the most predominant one. Consequently, 6 haplotype combinations were found in the population of which h1h5 haplogroup was the most frequent one while h1h3 haplogroup was the least frequent one. The sex-wise differences of distribution of haplotypes as well as haplogroups were found as nonsignificant. The broiler population did not follow the Hardy- Weinberg equilibrium for this locus. The differences of nucleotides at several locations were found in the haplotypes. Different demographic parameters were also studied with respect to the haplotype distribution in the population.